Socially and pedagogical aspects of animation activity - Danylo Kononchuk (Vasyl Stefanyk Precarpathian National University, 2018)
The actuality of animation activity, conditioned by the problem of creative development of personality and search of new directions of unity with sociocultural space of European community, is exposed in the article. It is marked expansion of directions of the use of animation activity in different scientific industries, to the necessity of her specification for social pedagogics in accordance with the socialpedagogical paradigm of social education as basis of development of modern socialpedagogical science and practice. The features of animation activity are described in a socialpedagogicalcontext. Keywords: animation, sociocultural animation, animation activity, pedagogical animation, socialpedagogical activity.